Dampak Pengembangan UMKM Pada Penyerapan Tenaga Kerja dan Pendapatan Masyarakat Di Wisata Alam Malino Kabupaten Gowa - Ramadhan, Muh Nur Rahmat; Hastuti, Diah Retno Dwi; Jamil, Muh (Journal Management & Economics Review (JUMPER), 2024)
This study aims to determine the impact of the development of Micro, Small and Medium Enterprises (MSMEs) by the community on income and employment in the Malino Nature Tourism area. The informants in this study were the Head of the Malino Cooperative and MSME Service, MSME actors. The analysis tools used were Data Reduction, Data Presentation, and Conclusion Drawing. The data collection techniques used were Observation, Interviews, and Documentation. The results of this study indicate that the income of MSME actors in the Malino Area shows an up and down trend. There are still several obstacles faced by the community in terms of increasing income. Such as, the government has not provided massive training, to several obstacles such as weather and tourist access to Malino tourism. Unpredictable weather is a problem that cannot be overcome, and weather is an obstacle for MSME actors in terms of increasing their income. In addition, employment absorption shows a very good trend. This is evidenced by MSME actors who in running their businesses need and absorb local workers. Of course this encourages to reduce the unemployment rate in the Malino Area. MSMEs have contributed to reducing unemployment rates through workforce absorption.